Relationship between Community Participation, Socio Economy and Organizational Capacity on Sustainable Development - Wan Abd Aziz, Wan Mohd Amin; Yahaya, Ibrahim; Ahmad Puad, Mat Som (2018)
This paper attempts to understand the influence of community participation, socio-economy and organizational capacity on the sustainability of community based tourism, focusing on homestay programs. This study has gathered data from 96 homestay’s operators from northern states of peninsular Malaysia. This study used path analysis approach to determine community participation and socio-economy factors that trigger organizational capacity and sustainable development. Based on the results, community participation and socioeconomy are correlated in indirect effect with sustainable development through organizational capacity. Thus the path-analysis indicates that the engagement of organizational capacity in the homestay program will correlate community participation and socio-economy toward sustainable development.